Effect of temperature on milk rheologic and thermophysical properties - Hlaváč Peter; Božiková Monika (Journal on Processing and Energy in Agriculture, 2011)
This article deals with rheologic and thermal properties of different types of milk. If we want to protect high standard of quality during the processing and storage of milk we need to know physical parameters which can evaluate the quality of food material. The most important properties are mainly mechanical and thermophysical parameters. The article presents the results from rheologic and thermophysical parameter measurements of milk with different fat content. For rheologic property measurement, the digital rotational viscometer Anton Paar DV-3P was used. Thermophysical properties were measured by Hot wire (HW) method. We measured the effects of temperature on rheologic parameters such as: dynamic and kinematic viscosity, fluidity and thermophysical parameters as: thermal conductivity and diffusivity. All the samples were measured in the temperature range (5-25)ºC in the laboratory settings. The results of the measurement showed that temperature and different fat content of milk have significant influence on milk rheologic and thermophysical parameters.